Management of the Leadership of Female Principals in Optimizing Teacher Performance During the Covid-19 Pandemic - Esa Kurnia Dahlan; Sunhaji Sunhaji (FONDATIA, 2022)
The unfinished pandemic of COVID-19 has changed the course of the education process. One of the key to the success of a educational institution today is the management and policies implemented by the principal as a leader. The purpose of this study is to find out the Management of Female Principal Leadership in Optimizing Teacher Performance During the Covid-19 Pandemic. This type of research is a field research with descriptive-qualitative method. Data collection techniques using observation, interview and documentation. This research was conducted at PAUD Wadas Kelir with the subject of the research, namely the Principal of PAUD Wadas Kelir. The results of this study show that: First, Head of PAUD Wadas Kelir Purwokerto developed a teacher performance optimization policy program during the covid-19 pandemic, in the form of the obligation to implement health protocols in the school environment, learning activities conducted from home and a combination of online-offline learning, as well as policies in learning innovations during the pandemic. Second, the headmaster's leadership style in optimizing the performance of PAUD Wadas Kelir Purwokerto teachers during the COVID-19 pandemic applies a democratic, consultative, and transformational leadership style. Third, the obstacles experienced by the head of PAUD Wadas Kelir include the lack of ability of teachers in operating technology as a learning medium, the lack of teacher ideas in presenting fun learning activities, and the background of the teachers' educational qualifications that are not appropriate.